2022
DOI: 10.5194/acp-22-15777-2022
|View full text |Cite
|
Sign up to set email alerts
|

Enviro-HIRLAM model estimates of elevated black carbon pollution over Ukraine resulted from forest fires

Abstract: Abstract. Biomass burning is one of the biggest sources of atmospheric black carbon (BC), which negatively impacts human health and contributes to climate forcing. In this work, we explore the horizontal and vertical variability of BC concentrations over Ukraine during wildfires in August 2010. Using the Enviro-HIRLAM modelling framework, the BC atmospheric transport was modelled for coarse, accumulation, and Aitken mode aerosol particles emitted by the wildfire. Elevated pollution levels were observed within … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…Nevertheless, changes up to ±4 • C were detected at a local scale or during specific synoptic conditions. Our previous study, conducted during more severe wildfires in 2010 but at some distance from burning areas [31], showed similar changes in the 2 m air temperature, reaching ±3 • C. Ref. [33] described that opposite air temperature changes can be even more significant, reaching up to ±6 • C at the local scale.…”
Section: Discussionmentioning
confidence: 57%
See 3 more Smart Citations
“…Nevertheless, changes up to ±4 • C were detected at a local scale or during specific synoptic conditions. Our previous study, conducted during more severe wildfires in 2010 but at some distance from burning areas [31], showed similar changes in the 2 m air temperature, reaching ±3 • C. Ref. [33] described that opposite air temperature changes can be even more significant, reaching up to ±6 • C at the local scale.…”
Section: Discussionmentioning
confidence: 57%
“…Our results show that the aerosol effects influenced the meteorological parameters near the surface. Most of the earlier studies have reported cooling effects due to the aerosols emitted from the wildfires [18][19][20]31]. In general, an elevated aerosol content (with prevailing BC and OC compounds) caused slight cooling, with greater agreement with a fine spatial resolution.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Notably, areas in proximity to the wildfire's origin recorded the highest average concentrations, peaking at 2.5μg/m 3 for BC and 15.0μg/m 3 for OM. Biomass combustion from wildfires is a significant source of atmospheric BC and OM (Savenets et al 2022;Coward et al 2022). The dispersion of ash containing BC and OM into the atmosphere, aided by rising air currents from wildfires, exhibits a lagged release.…”
Section: Analysis Of Potential Factors Influencing Water Quality Duri...mentioning
confidence: 99%